Integrating Burning and Insecticide to Reduce Fire Ant Impacts on Bobwhite Chicks - Amy Norton Johnson; C. Brad Dabbert; Robert B. Mitchell; Harlan G. Thorvilson (National Quail Symposium Proceedings, 2017)
Hatching northern bobwhite (Colinus virginianus) chicks experience a low survival rate when exposed to a significant number of foraging red imported fire ants (Solenopsis invicta; RIFA). We initiated a study in southeastern Texas to determine if a reduced rate of insecticide and/or prescribed burning could decrease the foraging activity of RIFA below the threshold that causes mortality of northern bobwhite chicks. Research sites were divided into burned and nonburned plots and individual plots randomly received one of 4 rates of insecticide treatment: 0, 50, 75 or 100% of the recommended label rate (1.68 kg/ha) of Amdro ® (hydramethylnon) insecticide bait (Ambrands, Atlanta, GA). Bait cup sampling of RIFA was conducted and differences in RIFA foraging activity were analyzed among treatments. As the rate of Amdro ® application increased, RIFA foraging activity declined. Data from 2002 and 2003 revealed a difference in mean number of foraging RIFA in insecticide treated plots versus control plots (P < 0.05) when testing for the main effect of insecticide treatment. The mean number of foraging RIFA in 2002 decreased approximately 34%, whereas the mean number of foraging RIFA in 2003 decreased approximately 39%. In both years, the mean number of foraging RIFA collected in bait cups in burned plots was not different from nonburned plots (P > 0.05).
Keywords: Amdro; Colinus virginianus; northern bobwhite; prescribed fire; red imported fire ant; Solenopsis invicta; Texas